2019
DOI: 10.1016/j.acra.2018.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Pulmonary Nodule Growth with Chest Tomosynthesis: A Human Observer Study Using Simulated Nodules

Abstract: The study indicates that chest tomosynthesis can be used to detect pulmonary nodule growth. Nodule size, dose level, and mismatch in position relative to the image reconstruction plane in the baseline and follow-up examination may affect the precision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The present study suffers from unknown "true" change in nodule size, issues which can be solved by using simulated nodules, such as the one from S€ oderman et al (19), which showed good performance of DTS in detection of nodule growth. However, other factors such as better definition of artificial nodule border, location according to the imaging plane, and fewer motion artefacts are circumstances that impair the ability to draw any direct conclusions to a clinical setting.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The present study suffers from unknown "true" change in nodule size, issues which can be solved by using simulated nodules, such as the one from S€ oderman et al (19), which showed good performance of DTS in detection of nodule growth. However, other factors such as better definition of artificial nodule border, location according to the imaging plane, and fewer motion artefacts are circumstances that impair the ability to draw any direct conclusions to a clinical setting.…”
Section: Discussionmentioning
confidence: 96%
“…Söderman et al. (19) investigated nodule growth on simulated nodules in DTS, and reported that the modality could be applicable, but nodule size, position, and dose level affected the precision of the measurements. Other studies have shown a small difference in size estimates between CT and DTS (20,21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation